The clinical performance and cost-effectiveness of two psychosocial assessment models in maternity care: The Perinatal Integrated Psychosocial Assessment study. Issue 2 (March 2022) - Chambers, Georgina M.; Botha, Willings; Reilly, Nicole; Black, Emma; Kingston, Dawn; Austin, Marie-Paule
Abstract: Problem: Although perinatal universal depression and psychosocial assessment is recommended in Australia, its clinical performance and cost-effectiveness remain uncertain. Aim: To compare the performance and cost-effectiveness of two models of psychosocial assessment: Usual-Care and Perinatal Integrated Psychosocial Assessment (PIPA). Methods: Women attending their first antenatal visit were prospectively recruited to this cohort study. Endorsement of significant depressive symptoms or psychosocial risk generated an 'at-risk' flag identifying those needing referral to the Triage Committee. Based on its detailed algorithm, a higher threshold of risk was required to trigger the 'at-risk' flag for PIPA than for Usual-Care. Each model's performance was evaluated using the midwife's agreement with the 'at-risk' flag as the reference standard. Cost-effectiveness was limited to the identification of True Positive and False Positive cases. Staffing costs associated with administering each screening model were quantified using a bottom-up time-in-motion approach. Findings: Both models performed well at identifying 'at-risk' women (sensitivity: Usual-Care 0.82 versus PIPA 0.78). However, the PIPA model was more effective at eliminating False Positives and correctly identifying 'at-risk' women (Positive Predictive Value: PIPA 0.69 versus Usual Care 0.41). PIPA was associated with small incremental savings for both True Positives detected and False Positives averted. Discussion: Overall PIPA performed better than Usual-Care as a psychosocial screening model and was a cost-saving and relatively effective approach for detecting True Positives and averting False Positives. These initial findings warrant evaluation of longer-term costs and outcomes of women identified by the models as 'at-risk' and 'not at-risk' of perinatal psychosocial morbidity.